Using 21st-century technologies to determine the cognitive capabilities of a 11,000-year-old Perak Man who had brachymesophalangia type A2 - Abdullah, Johari Yap; Saidin, Mokhtar; Ahmad Rajion, Zainul; Hadi, Helmi; Mohamad, Norshahidan; Moraes, Cicero; Abdullah, Jafri Malin (Penerbit Universiti Sains Malaysia (Penerbit USM), 2021)
Perak Man, named after the state where the skeleton was found, was the most complete skeleton found in Southeast Asia. The funerary artefacts indicate that Perak Man was highly respected, as he was buried at the centre of the highest cave in Lenggong, and he was the only person buried there. A copy of the original skull was made using computed tomography (CT) and 3D printing. Based on the internal structure of the reconstructed skull, the estimated intracranial volume (ICV) is 1,204.91 mL. The hypothetical face of Perak Man was reconstructed according to established forensic methods. Based on his presumed status, Perak Man was likely a respected person in the group and, perhaps, a shaman and the most knowledgeable person in the group regarding survival, hunting, gathering and other aspects of Palaeolithic daily life.